Pengembangan Media Pembelajaran GEMBARA Berbasis Android untuk Meningkatkan Hasil Belajar Murid pada Materi Bangun Datar Kelas IV SDN 7 Suwawa - Yulyanti Malapo; Gamar Abdullah; Andi Marshanawiah; Nur Sakinah Aries; Ade Mahniar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study addresses the limited availability of Android-based mathematics media that integrate content, video, games, and evaluation within a single application, and responds to this gap by developing GEMBARA (Gembira Belajar Bangun Datar) to help fourth-grade students at SDN 7 Suwawa learn the area and perimeter of plane figures. Using a Research and Development approach built on the ADDIE framework analysis, design, development, implementation, and evaluation the study involved 19 fourth-grade students (7 girls and 12 boys), with data collected through observation, questionnaires, tests, and documentation. Expert validation placed the medium's feasibility at an average of 93.1%, classified as “Very Feasible,” while responses from teachers and students placed its practicality at 95.8%, classified as “Very Practical.” Learning-outcome data gathered through pretest and posttest scores produced an N-Gain of 0.73 (72.53%), placed in the “High” category. Together, these results indicate that the Android-based GEMBARA medium is feasible, practical, and effective for strengthening fourth-grade students' understanding of plane-figure concepts.